D3.js Complete Developer Data Visualization Guide - Dichone, Paulo (Packt Publishing, 2020)
Bring data to life with the D3.js data visualization library, and get up to speed with JavaScript, HTML, and CSS to build stunning data visuals About This Video Learn to create a bar chart that can move dynamically Visualize earthquakes - both dynamically and as circles in the x-axis Get to grips with using the getElementById selector In Detail Effective visualization of data helps users analyze and gather insights about data, making complex data more accessible, understandable, and easy on the eye. If you want to create incredible graphs and data-driven visualizations from raw data and communicate information clearly and efficiently within your organization, work, and school, then enroll in this complete data visualization course covering the D3.js library. The course begins with an introduction to D3.js, and then teaches you how to create dynamic visualizations, scales, bar charts, and SVG paths. You'll then perform hands-on tasks such as earthquake visualization, creating a pie chart, and building a navigation page. The course then takes you through JavaScript fundamentals, along with covering arrays, loops, functions, and objects. Toward the concluding chapters, you'll get to grips with the document object model (DOM) and the browser object model (BOM). By the end of this course, you'll have gained a solid understanding of the basics of HTML, CSS, and JavaScript - the three main technologies necessary for building amazing visualizations using the D3.js library.